(untitled) (Research, Society and Development, 2021)
This study sought to develop and validate a software for teaching vaccination. This is a methodological study of the applied type aimed at developing an educational software for teaching-learning the content of vaccination, as well as validating its content and appearance, carried out in the state of Minas Gerais, Brazil, in 2018. It was used as methodological reference the Design Science and as theoretical reference the Learning Cone of Edgar Dale. DrawExpress Diagram was used for modeling, and Microsoft Visual Studio 2008 and Microsoft’s Visual Basic for Applications programming language were used to build the software. All information contained in the software was based on norms and guidelines of the Brazilian National Immunization Program. The content and appearance validation occurred with two different groups: nursing teachers/researchers (judges) and students (target audience). A questionnaire was used to evaluate the objectives, organization, information style, appearance, and motivation of the software. Two rounds of validation were performed. The software was developed and validated by eight faculty/researchers and 22 students, obtaining good evaluations. The Vaccine MegaCyber software was developed and validated, obtaining excellent evaluations, proving to be effective in the vaccination teaching-learning process, according to researchers in the field and the target audience, represented by the students, characterized as the end users of this technology. It is believed that this educational technology can be an important tool in the teaching-learning process of the vaccination content for undergraduate nursing students.